The Role Of Cultural Intelligence and Digital Technology In Multiplicational Leadership in the Global Era - Budi Priyono; Manlian RA Simanjuntak (International Journal of Social Welfare and Family Law, 2025)
In the era of globalization and digital transformation, organizations face new challenges in managing cultural diversity and technological complexity. Leaders are required to quickly adapt to the ever-changing global dynamics while fostering synergy within multicultural teams. This article aims to analyze how Cultural Intelligence (CQ) and digital technology can be integrated into a multiplication leadership model to enhance the effectiveness of global organizations. Using a qualitative approach based on literature studies, this research explores the three main dimensions of CQ—cognitive, motivational, and behavioral—as well as the application of digital technologies such as Artificial Intelligence (AI), Big Data, and virtual communication in leadership development. The findings indicate that leaders with high levels of CQ are more effective in leading multicultural teams and building harmonious cross-cultural connections. Meanwhile, the use of digital technology accelerates decision-making processes, mentoring, and collaboration within flexible and dynamic organizational structures. The integration of cultural intelligence and digital technology results in an adaptive, collaborative, and innovative leadership model. Examples of the implementation of this model in global companies such as Microsoft, Tesla, and Airbnb further reinforce the findings. This article provides practical contributions for organizations in designing training strategies and leadership models based on CQ and digital leadership to face global challenges more effectively and sustainably.